The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3109/03009742.2013.863382
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the prescription of intensive combination treatment strategies for early rheumatoid arthritis

Abstract: A heterogeneous set of factors highlights the complexity of prescribing ICTS for early RA in daily clinical practice. Future improvement strategies should stimulate the facilitators while at the same time addressing the barriers. The generalizability of these findings to other health care systems needs further examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…The barriers about side effects, perceived patient's resistance and non-compliance with the treatment are similar to those of rheumatologists prescribing an intensive treatment strategy (21). Our findings show that GPs want to be involved, without taking over the rheumatologist's tasks or entering their specialty.…”
Section: Comparison With Existing Literaturesupporting
confidence: 59%
See 1 more Smart Citation
“…The barriers about side effects, perceived patient's resistance and non-compliance with the treatment are similar to those of rheumatologists prescribing an intensive treatment strategy (21). Our findings show that GPs want to be involved, without taking over the rheumatologist's tasks or entering their specialty.…”
Section: Comparison With Existing Literaturesupporting
confidence: 59%
“…We developed an interview guide (Box 1) that was based on (a) literature on GPs' experiences to early RA management and (b) previous interviews with rheumatologists, nurses and patients regarding intensive treatment strategies for early RA in Flanders (15,17,21,22). Two authors (JS and SM) conducted the interviews.…”
Section: Data Collectionmentioning
confidence: 99%
“…Furthermore, the possibility to use a lower dose of GCs, while having the same efficacy, could benefit the implementation of COBRA-like strategies. Rheumatologists appear more reluctant to administer complex therapies with high dosages of GCs,22 23 40–42 although we showed that this approach is feasible in daily practice 35. den Uyl et al 36 reported similar results comparing an attenuated COBRA regimen with the original one in a moderately active eRA population.…”
Section: Discussionmentioning
confidence: 70%
“…The perception on GCs, however, remains ambiguous in both the patient's and the physician's mind. Thus many rheumatologists hesitate to prescribe GCs due to fear for side effects 22 23. Little is yet known about the optimal initial dose, treatment duration and administration route 24…”
Section: Introductionmentioning
confidence: 99%
“…[55][56][57] A heterogeneous set of factors has been identified that seem to influence prescription of intensive combination treatment for RA, including clinicians' personal faith in the treatment strategy, availability of staff support, lack of financial support, time constraints, and concerns regarding patients' perceptions. 58 Inappropriate practice change In contrast to the delays observed in utilization of other new treatments, biologic drugs enjoyed rapid uptake into clinical practice in the early 2000s after trials demonstrated that they reduce disease activity and improve quality of life in people with severe, active RA that is unresponsive to traditional DMARDs. Although these expensive drugs are acknowledged to represent a distinct advance in the treatment of RA and other inflammatory arthritides, expansion of their use to include people with earlier and less-severe disease preceded the demonstration of evidence establishing their value across these additional indications.…”
Section: Increasing the Value Of Clinical Researchmentioning
confidence: 98%